2021
DOI: 10.3390/ma14154239
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Crystallization and Supramolecular Self-Assembly of Spider Silk Inspired Protein at the Water-Air Interface

Abstract: Macromolecular assembly into complex morphologies and architectural shapes is an area of fundamental research and technological innovation. In this work, we investigate the self-assembly process of recombinantly produced protein inspired by spider silk (spidroin). To elucidate the first steps of the assembly process, we examined highly concentrated and viscous pendant droplets of this protein in air. We show how the protein self-assembles and crystallizes at the water–air interface into a relatively thick and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Previously, Mohammadi et al. showed that similar silk-like proteins can self-assemble at the water–air interface of a droplet in a manner that is both time- and RH-dependent . Furthermore, they noticed a significant difference in the β-sheet content between 40 and 80% RH, an observation consistent with our findings that the most dramatic change happens in the range of 45–65% RH.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, Mohammadi et al. showed that similar silk-like proteins can self-assemble at the water–air interface of a droplet in a manner that is both time- and RH-dependent . Furthermore, they noticed a significant difference in the β-sheet content between 40 and 80% RH, an observation consistent with our findings that the most dramatic change happens in the range of 45–65% RH.…”
Section: Resultssupporting
confidence: 91%
“…showed that similar silk-like proteins can self-assemble at the water–air interface of a droplet in a manner that is both time- and RH-dependent . Furthermore, they noticed a significant difference in the β-sheet content between 40 and 80% RH, an observation consistent with our findings that the most dramatic change happens in the range of 45–65% RH. The effect of the protein concentration on CA indicates that a moderate amount of protein is better provided that the film contains enough protein for full surface coverage.…”
Section: Resultssupporting
confidence: 90%
“…Measurements were performed with an energy exposure of 15 keV (0.82656 Å) using a silicon 111 monochromator and a beam size of 100 μm. Data were recorded using an Eiger X 9M detector with a pixel size of 75 μm × 75 μm, as reported previously ( 56 , 57 ). The measurements were carried out under ambient conditions at 50% RH.…”
Section: Methodsmentioning
confidence: 99%
“…The foams were fabricated through a very simple and scalable process, which involved gently introducing air bubbles into the 4RepCT solution. The process was continued until the stable foam was formed by the self-assembly of 4RepCT proteins at the air–water interface …”
Section: Bioengineering Of Protein-based Materialsmentioning
confidence: 99%